2019
DOI: 10.1371/journal.pone.0222750
|View full text |Cite
|
Sign up to set email alerts
|

Patient factors affecting successful linkage to treatment in a cervical cancer prevention program in Kenya: A prospective cohort study

Abstract: ObjectiveTo identify patient factors associated with whether women who screened positive for high-risk human papillomavirus (hrHPV) successfully accessed treatment in a cervical cancer prevention program in Kenya.MethodsA prospective cohort study was conducted as part of a trial of implementation strategies for hrHPV-based cervical cancer screening in western Kenya from January 2018 to February 2019. In this larger trial, women underwent hrHPV testing during community health campaigns (CHCs), and hrHPV+ women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…At the clinic 16 (25) Didn't ask 1 (2) No response 4 (6) Preferred location for treatment if needed Clinic 46 (72)…”
Section: Discussionmentioning
confidence: 99%
“…At the clinic 16 (25) Didn't ask 1 (2) No response 4 (6) Preferred location for treatment if needed Clinic 46 (72)…”
Section: Discussionmentioning
confidence: 99%
“…The trial demonstrated significantly higher levels of population-based uptake and adherence for self-collection HPV testing. Huchko et al, 2017 [ 46 ]; Oketch et al, 2019 [ 80 ]; Page et al, 2019 [ 81 ] Kenya Women Age: 25–65 years CRCT 4944 Intervention: Cervical cancer screening was carried out using HPV testing of self-collected specimens through community health campaigns Device- careHPV Control: HPV testing at health facilities Uptake of HPV testing Screening uptake was greater in communities assigned to community health campaigns compared to those assigned to receive screening through health facilities (60.0% vs 37.0%, P <0.001). Modibbo et al, 2017 [ 48 ] Nigeria Women residing in an urban area Age: 30–65 years RCT 400 (Intervention group: 200; Control group: 200) Intervention: HPV self-sampling kit directly mailed to the home address with a prepaid return envelope (or could drop off the completed kit at designated collection points in the community or the hospital).…”
Section: Resultsmentioning
confidence: 99%
“…The flow diagram for the patient component of this study has been published elsewhere [ 7 ] and is included here as a supporting file ( S1 Fig ). Demographic information on the participants can also be found in a supporting file ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…stigma) as contributing factors [ 5 , 6 ]. We have previously reported on patient factors associated with whether women who screened hrHPV+ presented for treatment [ 7 ]. The aim of the current research was to identify health systems-level barriers to treatment, including both structural and clinic-based barriers.…”
Section: Introductionmentioning
confidence: 99%